Dobrogea between 1916 and 1918 in German Historical Sources - Valentin Ciorbea (Annals: Series on History and Archaeology (Academy of Romanian Scientists), 2017)
The article examines some documents created by the German Stage Administration of Dobrogea, which began to organize itself since October 1916 on an area of 7.700km², which included the county of Constanţa and a strip in southern Tulcea. In the absence of historical sources destroyed by war and occupiers, the remaining historical sources from the German administration are essential for knowing the situation of an important area of the region between the Danubeand the Black Sea. Essential information is included in the Memorandum of the German Stage Administration of Dobrogea issued in mid April 1917. Knowledge of demographic realities is possible from the data in two statistics: Statistics of the Inhabitants o f the German Stages Administration in Dobrogea, 15 May 1917and Statistics of the Inhabitants of the German Stage Administration in Dobrogea, February 15, 1918. Another document, Report on Conversations that took place between commanders charged with the exploitation phase, supply officers and commanders of regiments and battalions, refers to 16 themes. “Curierul Dobrogei” periodical is published in German by the German Administration, later with a supplement in Bulgarian and Turkish. The German government printed Images from Dobrogea, a valuable collective volume, with the contributions of major German scientists.